Between Ramus, Alexander of Aphrodisias and Averroes. Francesco Vimercato’s Commentary to Book Twelve of Aristotle’s Metaphysics - Facca, Danilo (Peitho. Examina Antiqua, 2012)
What kind of causality does the Aristotelian Prime Mover exert on the heaven? Who “loves” the Prime Mover? Renaissance peripatetic philosopher, Francesco Vimercato, a “royal” teacher of “Greek and Latin philosophy” in Paris during the forties and the fifties of the 16th century tried to resolve these traditional puzzles that resulted from the exegesis of the Metaphysics XII, 6–7. His solution appears to be innovative, if compared to the ancient and the medieval ones. It seems partially to prefigure the last two decades’ interpretations of Aristotelian “theology”.